A Novel One-Sided Push-Out Test for Shear Connectors in Composite Beams - Shather, Luay M.; Al-Shuwaili, M. A. Hussein (Salehan Institute of Higher Education, 2025)
The small-scale push-out test (POT) is widely utilized to investigate the characteristic behavior of shear connectors as an available alternative to full-scale beam tests, which are often costly and time-consuming. However, several researchers have expressed issues regarding the POT specimen setup during testing due to inconsistencies between the results of POTs and beam bending tests. In this paper, a new configuration for a one-slab POT is developed to address these issues. To validate the developed method of testing, several POTs and OSPOTs were conducted and compared against each other and with those of previous research. The load-slip curves obtained from the OSPOTs were then evaluated against the curves obtained from four empirical expressions. Furthermore, a database of different POT configurations and setups, specifically 114 tests, selected from the previous research that employed the 19 mm shear stud, was analyzed in detail. Subsequently, the results of these tests and the proposed OSPOT method were compared with the predictions offered by several empirical equations. The results indicated that the results of the OSPOT are more consistent with the codes and empirical equations compared to typical POT. Hence, this OSPOT setup could be used as an efficient and economic option for the POT, as it has the potential to double the number of results for the same resources and simplify the casting procedure, which is particularly significant when numerous tests are required for the experimental campaign. Also, the OSPOT results revealed more ductile behavior for the shear studs, which is consistent with the full-scale beams’ testing.